2007
DOI: 10.1002/jcc.20857
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of a fast and accurate QM/MM potential method in Amber

Abstract: Version 9 of the Amber simulation programs includes a new semi-empirical hybrid QM/MM functionality. This includes support for implicit solvent (generalized Born) and for periodic explicit solvent simulations using a newly developed QM/MM implementation of the particle mesh Ewald (PME) method. The code provides sufficiently accurate gradients to run constant energy QM/MM MD simulations for many nanoseconds. The link atom approach used for treating the QM/MM boundary shows improved performance, and the user int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
451
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 393 publications
(454 citation statements)
references
References 48 publications
(56 reference statements)
3
451
0
Order By: Relevance
“…Test calculations have shown that this approach gives significantly better stability of the charge on QM atoms around the QM-MM interface than is observed if the QM link atom interacts only with other QM atoms not seeing the MM charge field. 26 In addition while our link atom approach introduces a slight displacement in position of the charge on the MM link atom to a dynamic charge on the link atom the overall effect is likely to be very minor. Also, the gradients are formally correctly dealt with when transferring the force on the QM link atom back to the atoms making up the QM-MM link pair and so this approach properly conserves energy.…”
Section: Qm/mmmentioning
confidence: 98%
See 4 more Smart Citations
“…Test calculations have shown that this approach gives significantly better stability of the charge on QM atoms around the QM-MM interface than is observed if the QM link atom interacts only with other QM atoms not seeing the MM charge field. 26 In addition while our link atom approach introduces a slight displacement in position of the charge on the MM link atom to a dynamic charge on the link atom the overall effect is likely to be very minor. Also, the gradients are formally correctly dealt with when transferring the force on the QM link atom back to the atoms making up the QM-MM link pair and so this approach properly conserves energy.…”
Section: Qm/mmmentioning
confidence: 98%
“…For DFTB calculations we use a link atom scheme developed as part of the re-writing of AMBER's semi-empirical QM/MM method is used. 26 This approach is similar to that used by Dynamo, 36 where the link atom is treated as part of the covalent bond between the QM and MM atoms bonded across the interface. Each time an energy or gradient calculation is to be done the link atom coordinates are automatically generated from the current coordinates of the QM and MM atoms making up the QM-MM covalent pair.…”
Section: Qm/mmmentioning
confidence: 99%
See 3 more Smart Citations